MANAGEMENT of POSTPARTUM MIDWIFERY CARE on Mrs. J WITH ENGORGEMENT of THE BREAST - Hasanah, Nurul Zaitun; Pasaribu, Riska Susanti; Manurung, Basaria; Sinaga, Rosmani; Ginting, Siska Suci Triana; Angkat, Rani M (Mitra Husada Health Internasional Conference (MIHHICo), 2024)
Breast care during the postpartum period is very important for mothers to increase breast milk production to stimulate the breast milk glands. Breast care performed during the puerperium is very beneficial for mothers in addition to increasing breast production and preventing breast sagging during breastfeeding. Breasts are a mother’s precious "asset" for her baby, with which she can provide the best and quality food called breast milk. Postpartum breast care is breast care performed on postpartum mothers to improve blood circulation and prevent blockage of the milk ducts so as to facilitate breastfeeding. The implementation of breast care starts as early as possible, namely 1-2 days after the baby is born and is done twice a day.